A pocket full of posies: the spatial distribution of children’s diseases in early Johannesburg from 1923-1925 - Geoghegan, Neave Anne (My University, 2022)
This study focuses on the medical and surgical records of the Transvaal Children’s Memorial Hospital from its opening in 1923 until 1925. These archives allowed for the investigation of the spatial distribution of children’s diseases in Johannesburg over a three-year period through a process of manual mapping. The results produced were off-set against public health perceptions and legislations of the period. These publications broadly created the impression that social and sexual diseases were race-based and that spatial and social segregation was necessary to create a healthy and hygienic white city. However, the study showed no clear spatial trends of disease and demographics which revealed that most diseases were prevalent both in poorer and wealthier socio-economic white suburbs. These results indicated a high degree of ethnic intermingling within the white population. This project is situated within Medical and Health Geography and provides a more nuanced understanding if health and well-being within the white population of Johannesburg as well as a better understanding of diseases in children.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science (Archaeology)